Pembatalan Akta Hibah dalam Perkara Waris: Studi Kasus Putusan Pengadilan - Farah Hamdah Rahmawati; Syaifuddin Zuhdi (SIGn Jurnal Hukum, 2022)
This study examines and analyzes grant deed cancellation in inheritance cases based on Decision No. 0492/Pdt.G/2020/PA.Klt. This study uses a normative juridical research method. The data was collected using literature study techniques on primary, secondary, and tertiary legal materials. The collected legal material is then analyzed using qualitative data analysis methods with a statute approach and a case approach which will then conclude the object of the research. The results show that the cancellation of grant deeds in inheritance cases is based on Decision No. 0492/Pdt.G/2020/PA.Klt consists of several of the Judge’s considerations. First, Article 211 of the Compilation of Islamic Law regulates that grants from parents to their children can be equalized with inheritance. Second, Article 832 of the Civil Code and Article 174 section (1) of the Compilation of Islamic Law regulates that those entitled to become inheritors are blood-related families. Third, Article 841 and Article 842 of the Civil Code and Article 185 section (1) of the Compilation of Islamic Law regulates the rights transferred from inheritor to substitute inheritor. In addition, the transfer of the right from someone who dies to their inheritor applies automatically because of Allah’s provisions in Q.S. An-Nisa’ verse 7. Therefore, it is recommended for the plaintiffs and defendant to file a claim for certificate cancellation in the Administrative Courts. Proportionality of inheritance distribution: the defendant gets 3/6 inheritance, and three substitute inheritors each get 1/6 inheritance. Thus, the principle of justice can be felt and implemented by and for inheritance and substitute inheritors.